Analisis Perbedaan Goal Orientation Berdasarkan Tingkat Ekonomi Peserta Didik - Marwan, Marwan (TSAQOFAH, 2025)
Goal orientation is one of the developments of learning motivation theory with a belief pattern that leads to different ways of approaching, using and responding to achievement situations. One of the factors that influences goal orientation is economic level. The role of education in several developing countries has highlighted the problem of differences in the level of achievement of learning outcomes between schools, namely differences in the socio-economic status background of students which cause large differences in social levels in schools, thus encouraging the development of schools to achieve maximum learning achievement. This study aims to determine the differences in goal orientation of students who have differences in economic levels. The research method used is qualitative research with a descriptive approach to describe the picture of the differences in goal orientation of students. The results of the study showed that students who are at the middle economic level have a mastery goal type because there is an aspect of social support that supports students in understanding the lesson well. Meanwhile, students who have a performance goal type are at the lower economic level. This is because they get less social support due to their low economic level.